2023
DOI: 10.1002/mp.16231
|View full text |Cite
|
Sign up to set email alerts
|

Sub‐second photon dose prediction via transformer neural networks

Abstract: Background: Fast dose calculation is critical for online and real-time adaptive therapy workflows. While modern physics-based dose algorithms must compromise accuracy to achieve low computation times, deep learning models can potentially perform dose prediction tasks with both high fidelity and speed. Purpose: We present a deep learning algorithm that, exploiting synergies between transformer and convolutional layers, accurately predicts broad photon beam dose distributions in few milliseconds. Methods: The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Transformers-based dose prediction models have been proposed in recent years. 12 , 25 , 26 As a kind of typical transformers-based DL model, UNETR has never been used in dose prediction. 27 Research from Osman et al 28 showed that U-Net, attention U-Net, residual U-Net, and attention Res U-Net for H&N plans from OpenKBP-Grand Challenge data 7 had an almost comparable performance for voxel-wise dose prediction.…”
Section: Discussionmentioning
confidence: 99%
“…Transformers-based dose prediction models have been proposed in recent years. 12 , 25 , 26 As a kind of typical transformers-based DL model, UNETR has never been used in dose prediction. 27 Research from Osman et al 28 showed that U-Net, attention U-Net, residual U-Net, and attention Res U-Net for H&N plans from OpenKBP-Grand Challenge data 7 had an almost comparable performance for voxel-wise dose prediction.…”
Section: Discussionmentioning
confidence: 99%
“…DAM’s main application in robust treatment planning and robust evaluation against inter-fraction movements involves sampling patient anatomies and calculating the corresponding dose distributions. With prediction times of few milliseconds per generated anatomy, DAM offers huge speed-up possibilities for plan evaluation when coupled to fast dose calculation algorithms (Perkó et al 2016 , Pastor-Serrano and Perkó 2022a , 2022b , Pastor-Serrano et al 2022 ). Few (3–5) representative scenarios corresponding to points around mean of the posterior distribution can be sampled to be used for scenario based robust optimization, which may translate into a dosimetric advantage or be used for margin reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, it has been applied in various domains such as image classification, target detection, and semantic segmentation, etc. Due to the lack of global feature acquisition in CNN, researchers have employed the transformer and developed several superior dose prediction models in combination with other DL models [74] , [75] , [76] , [77] , [78] , [79] , [80] , [81] . Wen et al [80] argue that existing DL models overlook the isodose lines and gradient information in dose maps.…”
Section: Dose Predictionmentioning
confidence: 99%
“… For most isodose volumes,DSC > 0.91. Yue et al [75] /2022 Nasopharyngeal carcinoma:161 Training set:130 Validation set:11 Test set:20 3D U-Net Distance map Dose map The predicted dose error and DVH error are 7.51 % and 11.6 % lower than the mask-based method Jiao et al [76] /2023 Rectal cancer:120 Cervical cancer:42 Training set:116 Validation set:12 Testing set:34 Super-pixel-level GCN CT images Dose map HI 0.352;ΔD 95 0.150; ΔD mean 2.40E-2; ΔD max 1.68E-2 Pastor-Serrano et al [77] /2022 Training set:17 with disease sites of brain, head neck, lung, abdomen and pelvis Validation set:10 % of training set’s CT slices Test set:584 beam dose distributions iDoTA CT images Dose distribution Gamma pass rate in 50 ms:97.72 ± 1.93 %. Pass rate in 6–12 s:99.51 ± 0.66 %, average relative dose error:0.75 ± 0.36 %.…”
Section: Dose Predictionmentioning
confidence: 99%